Room temperature carbon monoxide oxidation based on two-dimensional gold-loaded mesoporous iron oxide nanoflakes. Issue 61 (16th July 2018) - Kaneti, Yusuf Valentino; Tanaka, Shunsuke; Jikihara, Yohei; Nakayama, Tsuruo; Bando, Yoshio; Haruta, Masatake; Hossain, Md. Shahriar A.; Golberg, Dmitri; Yamauchi, Yusuke
Abstract : A room-temperature catalyst for carbon monoxide oxidation based on gold-loaded mesoporous maghemite nanoflakes has been developed. Abstract : In this work, we fabricate a highly effective catalyst for carbon monoxide oxidation based on gold-loaded mesoporous maghemite nanoflakes which exhibit nearly 100% CO conversion and a very high specific activity of 8.41 molCO gAu −1 h −1 at room temperature. Such excellent catalytic activity is promoted by the synergistic cooperation of their high surface area, large pore volume, and mesoporous structure.